The impact of customer performance on IMC outcomes: firm size moderation in the inter-country context - Butkouskaya, Vera (2021)
Purpose. Taking the customer-centric nature of integrated marketing communications (IMC), this article investigates the specific role of customer performance in IMC effectiveness in various size companies applying inter-country context. Design/methodology/approach. The sample consists of the primary data from developed (Spain) and developing (Belarus) economies. A total of 540 manager respondents participated in the survey. The article uses structural equation modeling and multi-group analysis for analysis. Findings. When taking into consideration, customer performance affects the IMC outcome on the market and financial performance. The customer performance role varies in firms of various sizes and small- and medium -sized enterprises (SMEs) operating both in developed and developing economies. Research limitations/implications. The research underlines the significant role of customer performance in IMC implementation, which stimulates further investigation on the topic. It also closes the gap in the IMC outcomes analysis in SMEs operating in developed and developing economies. Practical implications. Customer evaluation plays a vital role in the IMC outcomes for market growth and financial returns. SMEs and larger companies implement IMC with different levels of effectiveness. SMEs with IMC implementation can gain an advantage over larger rivals and improve their market position. Moreover, the study generalizes the results by applying inter-country context. Originality/value. This is a pioneering study of the complex IMC outcomes model under firms' size moderate conditions. The research applies an inter-country context.